EUS-guided left lobe liver biopsy: Safer modality with similar diagnostic yield as right lobe: a pilot study - Sharma, Mithun; Lakhtakia, Sundeep; Jagtap, Nitin; Sekaran, Anuradha; Kalapala, Rakesh; Jahangeer, Basha; Kulkarni, Anand; Ramchandani, Mohan; Gupta, Rajesh; Samudraala, Swapna; Khanna, Juhi; Nagaraja, Padaki; Iyengar, Sowmya; Gora, Baker Ali; Rao, Guduru Venkat; Reddy, Nageshwar (Endoscopy International Open, 2023)
Background and study aims Percutaneous liver biopsy is traditionally done on the right lobe of the liver. Endoscopic ultrasound-guided liver biopsy (EUS-LB) can be performed on either the left or right lobe or as a combined bi-lobar biopsy. Earlier studies did not compare the benefit of bi-lobar biopsies to single-lobe biopsy for reaching a tissue diagnosis. The current study compared the degree of agreement of pathological diagnosis between the left lobe of the liver compared to right-lobe and with bi-lobar biopsy.Patients and methods Fifty patients fulfilling the inclusion criteria were enrolled in the study. EUS-LB with a 22G core needle was performed separately on both the liver lobes. Three pathologists, who were blinded to the site of biopsy independently reviewed the liver biopsies. Sample adequacy, safety, and concordance of pathological diagnosis between left- and right-lobe biopsy of the liver were analyzed.Results The pathological diagnosis was made in 96 % of patients. Specimen lengths from the left lobe and the right lobe were 2.31 ± 0.57 cm and 2.28 ± 0.69 cm, respectively (P = 0.476). The respective number of portal tracts were 11.84 ± 6.71 versus 9.58 ± 7.14; P = 0.106. Diagnosis between the two lobes showed substantial (κ = 0.830) concordance. Left-lobe (κ value 0.878) and right-lobe (κ = 0.903) biopsies showed no difference when compared with bi-lobar biopsies. Adverse events were observed in two patients, both of whom had biopsies of the right lobe.Conclusions EUS-guided left-lobe liver biopsy is safer than right-lobe biopsy with similar diagnostic yield.